The cotton trade and Brazilian foreign commerce during the industrial revolution - Pereira, Thales Augusto Zamberlan (2017)
This dissertation provides a new interpretation for the rise and subsequent decline of Brazil as a cotton supplier to the British textile sector during the Industrial Revolution. Between 1791 and 1801, northeast Brazilachieved a market share of 40 percent in Liverpool. Contrary to what scholars previously argued,the chief cause for the rise of Brazil as a major cotton exporterwas its superior cotton fiber for the new calico and muslin textiles produced in Britain. Notwithstanding the initial success, Brazilian cotton exports stagnated after 1819. Previous interpretations argued that the decline of Brazilian cotton plantations was a result of labor shortagesand high inland transport costs. This dissertation instead provides evidence showing that cotton regions in Brazil had in fact a high density of slaves. Likewise, transport costs represented a small fraction of cotton market prices. For cotton planters, the largest economic burden was the fiscal policy implemented by the central government after 1808. The need to increase revenues led the central government to tax the most important commodities at the time. Export taxes represented the largest cost for cotton production in Brazil until the 1840s. As regional governments could not tax imports, they were left with little resources to invest in infrastructure projects that could offset the increasing costs of taxation. In the end, higher production costs reduced Brazil\'s ability to face the challenge of new competitors in the international cotton market during the nineteenth century.